2009
DOI: 10.1159/000194271
|View full text |Cite
|
Sign up to set email alerts
|

eNOS Activation Induced by a Polyphenol-Rich Grape Skin Extract in Porcine Coronary Arteries

Abstract: Background/Aims: Drinking red wine is associated with a decreased mortality from coronary heart diseases. This study examined whether polyphenols contained in a grape skin extract (GSE) triggered the endothelial formation of nitric oxide (NO) and investigated the underlying mechanism. Methods: Vascular reactivity was assessed in organ chambers using porcine coronary artery rings in the presence of indomethacin (a cyclooxygenase inhibitor) and charybdotoxin plus apamin (inhibitors of endothelium-derived hyperpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 82 publications
3
37
0
Order By: Relevance
“…12) Phosphorylation of eNOS at Ser-1177 has been found to be associated with increases in enzyme activation and NO production. 15) Furthermore, several studies have reported that polyphenols such as epigallocatechin-3-gallate, 21) delphinidin, 22) resveratrol, 23) and PAs from grape skin extract 24) increased the phosphorylation of eNOS. Evaluation of persimmon leaf PA-stimulated phosphorylation in HUVECs revealed that ex vivo persimmon leaf PAs at the maximal relaxation concentration caused time-dependent phosphorylation not only of eNOS (Ser-1177), but also of its upstream kinase Akt (Ser-473) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…12) Phosphorylation of eNOS at Ser-1177 has been found to be associated with increases in enzyme activation and NO production. 15) Furthermore, several studies have reported that polyphenols such as epigallocatechin-3-gallate, 21) delphinidin, 22) resveratrol, 23) and PAs from grape skin extract 24) increased the phosphorylation of eNOS. Evaluation of persimmon leaf PA-stimulated phosphorylation in HUVECs revealed that ex vivo persimmon leaf PAs at the maximal relaxation concentration caused time-dependent phosphorylation not only of eNOS (Ser-1177), but also of its upstream kinase Akt (Ser-473) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3-kinase/ Akt signaling pathway is triggered by the polyphenolinduced intracellular formation of reactive oxygen species predominantly superoxide anions in endothelial cells [5, 68,77]. A similar mechanism of eNOS activation has been observed in response to a grape seed extract [35], grape skin extract [68], purple grape juice [5], strawberry powder rich in polyphenols [36], and epigallocatechin-3-gallate [67], a major flavonoid from the flavan-3-ol subclass found in green tea. In addition, polyphenols cause within minutes the phosphorylation of eNOS, and this effect persists for several hours indicating a sustained activation of eNOS.…”
Section: Role Of Intracellular Calciummentioning
confidence: 99%
“…Indeed, it is now accepted that polyphenols could prevent many diseases such as cancers (Yang et al, 2009;Korkina et al, 2009;Khan et al, 2009;Bracke et al, 2008;Franklin and McCubrey, 2007), cardiovascular (Madeira et al, 2009;Jones et al, 2011;Kumar et al, 2008;Agouni et al, 2009;Walter et al, 2008;SchiniKerth et al, 2011;Sall Diallo et al, 2008;Sarr et al, 2006 ; and degenerative diseases (Mollnau et al, 2006;Chen et al, 2007;Berrino, 2002;Meydani, 2002;Meydani, 2001). Encouraging the consumption of fruits and vegetables is now a major public health recommendation.…”
Section: Discussionmentioning
confidence: 99%